2019
DOI: 10.3390/app9235231
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Attachment of Conjugated Gold Nanoparticles to a Decellularized Tissue Scaffold

Abstract: Decellularized allograft tissue is used for a wide array of tissue injuries and repair with tenons and ligament repair being among the most common. However, despite their frequent use there is concern over the lengthy inflammatory period and slow healing associated with allografts. One promising solution has been the use of nanoparticles. There is currently no easy, fast method to achieve consistent conjugation of nanoparticles to tissue. The available conjugation methods can be time-consuming and/or may creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Bellrichard et al take a slightly different approach to engineering a scaffold. The authors use decellularized tendon as the scaffold material but augment the scaffold with gold nanoparticles with the goal of reducing the inflammatory response [5]. In this proof of principle study, the authors showed that they could successfully attach gold nanoparticles to the ECM scaffolds using genipin crosslinking and that these gold nanoparticles had no detrimental effects on cell viability or cell attachment.…”
mentioning
confidence: 99%
“…Bellrichard et al take a slightly different approach to engineering a scaffold. The authors use decellularized tendon as the scaffold material but augment the scaffold with gold nanoparticles with the goal of reducing the inflammatory response [5]. In this proof of principle study, the authors showed that they could successfully attach gold nanoparticles to the ECM scaffolds using genipin crosslinking and that these gold nanoparticles had no detrimental effects on cell viability or cell attachment.…”
mentioning
confidence: 99%